Structural Analysis of the Northern Ringvassøy-Loppa Fault Complex in the Southwestern Barents Sea - Saadi, Tauqeer Ahmad (2014)
The northern Ringvassøy-Loppa Fault Complex consists of extensional faults which separate the Tromsø and Hammerfest basins in south; the Loppa High and Tromsø Basin in center; and the Polhem Subplatform and Tromsø Basin in the northernmost part. 2D seismic interpretation has been carried out, to figure out general fault dips, location of fault nucleation, and detachment zones. In addition to this, basin modelling has been performed to investigate stretching factors. The northern Ringvassøy-Loppa Fault Complex consists of extensional faults which separate the Tromsø and Hammerfest basins in south; the Loppa High and Tromsø Basin in center; and the Polhem Subplatform and Tromsø Basin in the northernmost part. 2D seismic interpretation has been carried out, to figure out general fault dips, location of fault nucleation, and detachment zones. In addition to this, basin modelling has been performed to investigate stretching factors.